A Retrospective Study Comparing Mortality Rates between Vaccinated and Unvaccinated Kidney Transplant Recipients - Fayyaz, Anaam; Pozzerle, Judy; Antony, Suresh J. (Infectious Disorders - Drug Targets, 2024)
Background: With the emergence of vaccines for COVID-19, mortality and severity of disease have decreased. However, patients with certain comorbidities, such as immunosuppression, CKD, and renal transplant, still have higher mortality rates as compared to the general population. Current data suggests that the risk of developing COVID-19 among transplant patients was reported to be about 5%, which is significantly higher than the risk rate of 0.3% in the general population. Studies utilizing larger sample sizes (i.e., multiple cohorts, sites, hospitals) comparing COVID-19 outcomes among renal transplant patients with a control group are lacking. Objective: The purpose of this descriptive study was to compare the mortality rate between vaccinated and unvaccinated kidney transplant recipients. Methods: Participants were recruited at a community-based transplant clinic in West Texas. Results: Among the group of participants who tested positive for COVID-19 between 2020 and 2022, higher mortality rates and longer hospital stays were noted among those unvaccinated (72% unvaccinated had greater than 5-day length of stay vs. 33% vaccinated). Conclusion: Our study suggests that vaccination against COVID-19 decreases mortality rates in kidney transplant recipients.
Keywords: kidney